Analisis Perbandingan Algoritma Linear Search dan Binary Search dalam Efisiensi Pencarian Data - Hilman Firmansyah; Eggi Julian; Atep Ruhiat (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2025)
The rapid development of information technology has led to a significant increase in data volume, thus requiring information systems to perform data search processes quickly and efficiently. Search algorithms are a crucial component in determining system performance. This study aims to analyze and compare the efficiency of Linear Search and Binary Search algorithms in the data search process. The method used is a literature study with a descriptive and comparative approach to several relevant national journals. The results of the analysis show that Linear Search has the advantage in terms of flexibility because it does not require sorted data, but has a time complexity of O(n) making it less efficient for large datasets. In contrast, Binary Search has a time complexity of O(log n) and has proven to be more efficient on large, sorted datasets. Therefore, the selection of a search algorithm must be adjusted to the characteristics and conditions of the data so that the system can work optimally.